Implementation of Moodle, an open-source solution for Team Based Learning - Reid Proctor; Renee Hayslett (Journal of Teaching and Learning with Technology, 2024)
Conventional Team-Based Learning (TBL) uses a paper-based system to deliver a team-quiz component of the instructional method. We observed the use of this paper-based system in various settings and identified it could be challenging in a large classroom. Challenges include distributing paper answer cards, time to grade them, and additional personnel required to facilitate the process. The need for an electronic platform to reduce the logistical burdens of TBL was identified. We implemented Moodle as a secondary learning management system specifically configured to support team activities. Moodle supports an answer until correct function along with additional quiz question formats such as fill-in-the-blank and select all that apply, thus allowing greater flexibility compared to the paper-based system. In addition to supporting the team-quiz, this instance of Moodle has been used to effectively support other components of TBL. Two classes of professional pharmacy students were surveyed to capture perceptions of this novel use of the Moodle system. In addition, system usage data was also collected. Ninety-four percent of the students surveyed indicated that the Moodle system had worked well for each TBL session. Since the Fall of 2018, we have used this system to support delivering over 360 TBL class sessions with no technical incidents reported. This novel use of Moodle to support TBL has proven to be effective, reliable, and cost friendly. Further development and application of Moodle to support TBL is warranted.